Using Digital Games to Promote Equity in Career and Health Education: A Prototype of Caduceus Quest - McCammon, Ellen; Law, Jessica; Tyler, Crystal; Arrington, Mason; Jagoda, Patrick; Gilliam, Melissa (Urban education (Beverly Hills, Calif.), 2024)
Black and Latinx adolescents in urban schools can derive numerous benefits from tailored career and health education. However, many factors may prevent schools and teachers from offering such programing. To address the need for career and health education, we prototyped Caduceus Quest, a theory-based, digital role-playing game designed to provide information on health and biomedical science careers and sexual health (specifically HIV) for Black and Latinx adolescents. Forty high-school-aged adolescents participated in small group sessions to playtest the prototype. Post-intervention, adolescents reported increased interest in health and biomedical science careers, as well as HIV knowledge and PrEP awareness.